Choice of fields of study of Canadian university graduates: the role of gender and their parents' education - Brahim Boudarbat; Claude Montmarquette (Institute for the Study of Labor (IZA), 2007)
This paper examines the determinants of the choice of field of study by university students using data from the Canadian National Graduate Survey. The sample of 18,708 graduates holding a Bachelor degree is interesting in itself knowing that these students completed their study and thus represent a pool of high quality individuals. What impact expected post-graduation lifetime earnings have in choosing their field of study respectively to their non pecuniary preferences? Are these individuals less or more influenced by monetary incentives on their decision than was found in previous literature with samples of university students not all completing their studies successfully? Unlike existing studies, we account for the probability that students will be able to find employment related to their field of study when evaluating lifetime earnings after graduation. The parameters that drive students' choices of fields of study are estimated using a mixed multinomial logit model applied to seven broadly defined fields. Results indicate that the weight put by a student on initial earnings and earnings' rate of growth earnings depends upon the education level of the parent of the same gender. Surprisingly, lifetime earnings have no statistically significant impact when the parent of the same gender as the student has a university education. Results show that men are, in general, more sensitive than women to initial income variations, whilst women are more sensitive than men to the earnings' rate of growth variations. Marital status, enrolment status and the vocation identified with each field of study are influential factors in students' choices. From a policy perspective, a substantial increase in lifetime earnings, while all other factors remain constant, would be necessary to draw students into fields of study they are not inclined to choose initially
urn:nbn:de:101:1-20080425442
Keywords: 330; Studienfach; Berufswahl; Lohn; Geschlecht; Familiensoziologie; Schätzung; Kanada